Characteristics of instant rice in several corn varieties. Issue 2 (July 2021) - Layuk, P; Salamba, H; Lintang, M; Karouw, S; Abdullah, N
Abstract: The research aimed to process corn kernels into instant corn rice. Corn kernels are ground into grits then pre-gelatinized by churning for 25 minutes at a temperature of 85-93 0 C with a ratio of grits and water (1: 4) then dried to become instant corn rice. The results showed that pre-gelatinization had an effect on yield and product characteristics such as bulk density, porosity, water absorption rate, dehydration and growth rate. The highest yield of instant corn rice was Manado Kuning at 89%. Cook time ranges from 7-10 minutes and the development rate is 110-130%. Types of varieties and duration of freezing affect the characteristics of instant corn rice. Freezing time increases bulk density, porosity, swelling rate and reduces rehydration ratio and water absorption rate. The best treatment was the Manado Kuning corn variety with a freezing time of 48 hours resulting in the highest bulk density, porosity and dehydration level where the bulk density met US standards for parboiled rice, which was between 0.40 to 0.42 g/ml.